Research on the next generation internet based Chinese terrestrial ecosystem flux research network - Xiao-han LIU; Chao WU; Ze LUO; Bao-ping YAN; Wen-qing LI; Wen SU; Hong-lin HE (Tongxin xuebao)
For the actual demand for carbon cycle research in China,from 2012 to 2013,we start the research and development on IPv6-based Chinese terrestrial ecosystem flux research network (CNGI/ChinaFLUX).IPv4/IPv6-based real-time carbon flux observation system in ten field stations was set up.Data acquisition,data transmission was set up,data storage and sharing from flux observation tower to field station were completed,then to data center.Researchers develop a series of applications in CNGI/China FLUX network.